Effects of reducing processed culinary ingredients and ultra-processed foods in the Brazilian diet: a cardiovascular modelling study. Issue 1 (8th September 2017) - Moreira, Patrícia VL; Hyseni, Lirije; Moubarac, Jean-Claude; Martins, Ana Paula B; Baraldi, Larissa G; Capewell, Simon; O'Flaherty, Martin; Guzman-Castillo, Maria
Abstract: Objective: To estimate the impact of reducing saturated fat, trans -fat, salt and added sugar from processed culinary ingredients and ultra-processed foods in the Brazilian diet on preventing cardiovascular deaths by 2030. Design: A modelling study. Setting: Data were obtained from the Brazilian Household Budget Survey 2008/2009. All food items purchased were categorized into food groups according to the NOVA classification. We estimated the energy and nutrient profile of foods then used the IMPACT Food Policy model to estimate the reduction in deaths from CVD up to 2030 in three scenarios. In Scenario A, we assumed that the intakes of saturated fat, trans -fat, salt and added sugar from ultra-processed foods and processed culinary ingredients were reduced by a quarter. In Scenario B, we assumed a reduction of 50 % of the same nutrients in ultra-processed foods and processed culinary ingredients. In Scenario C, we reduced the same nutrients in ultra-processed foods by 75 % and in processed culinary ingredients by 50 %. Results: Approximately 390 400 CVD deaths might be expected in 2030 if current mortality patterns persist. Under Scenarios A, B and C, CVD mortality can be reduced by 5·5, 11·0 and 29·0 %, respectively. The main impact is on stroke with a reduction of approximately 6·0, 12·6 and 32·0 %, respectively. Conclusions: Substantial potential exists for reducing the CVD burden through overall improvements of the Brazilian diet. This might require reducing the penetration of ultra-processed foods by means of regulatory policies, as well as improving the access to and promotion of fresh and minimally processed foods.